Is there a 'suboptimal' woody species height? A response to Scheffer et al. (January 2015) - McGlone, Matt S.; Richardson, Sarah J.; Jordan, Gregory J.; Perry, George L.W.
Highlights: We challenge the concept that intermediate woody species heights are suboptimal. There is no bimodality in woody species heights at a regional flora scale. Claims that there is a deficit in 8–10 m high species are incorrect. Global plant trait databases under-represent shrubs and over-represent forests.